Approaches to accident investigation by investigators from different cultures - Li, Wen-Chin; Young, Hong-Tsu; Wang, Thomas; Harris, Don (Cranfield University, 2009)
Cultural characteristics play a significant part in aviation (Helmreich & Merritt, 1998). The collective nature of Chinese society is consistent with broad, contextual view of the world and their belief that events are highly complex and determined by many factors. On the other side, the individualistic nature of Western society seems consistent with the focus on particular objects in isolation from their context and with Westerners’ belief that they can know the rules governing objects and therefore can control the objects’ behavior (Nisbett, 2003). Westerners have a strong interest in categorization, which helps them to know what rules to apply to the objects, and formal logic plays a role in problem solving. Chinese attend to objects in their broad context. The world seems more complex to Chinese than to Westerners, and understanding events always requires consideration of many factors that operate in relation to one another in no simple way. From the I-Ching (ancient Chinese philosophical book), ‘for misery, happiness is leaning against it; for happiness, misery is hiding in it. Who knows whether it is misery or happiness? There is no certainty. The righteous suddenly becomes the vicious; the good suddenly becomes the bad’. Chinese is less concerned with finding the truth than with finding the harmony way to live in the world. As the result, Chinese failure to develop science can be attributed in part to lack of curiosity to the true, but the absence of a concept of nature would have blocked the development of science in any case.
Keywords: Aviation Safety, Cross-cultural research, Human Errors, Human Factors Analysis and Classification System